Bird strike : the crash of the Boston Electra - Kalafatas, Michael N. (Brandeis University Press ; Published by University Press of New England, 2010)
An intriguing and thoughtful investigation of New England's first major air disaster, caused by a massive bird strike, a half-century ago.